A taxonomic study on Centaurea sect. Rhizocalathium and C. sect. Pseudoseridia (Asteraceae, Cardueae–Centaureinae) in Iran - Negaresh, Kazem; Rahiminejad, Mohammad Reza; Ranjbar, Massoud (Phytotaxa, 2014)
A taxonomic review of Centaurea sect. Rhizocalathium Tzvelev and C. sect. Pseudoseridia Wagenitz in Iran was carried out. The latter, with only one species, Centaurea stevenii, is reported here as new to Iran. In Centaurea sect. Rhizocalathium, C. lasiorhiza is treated as a correct name, C. ispahanica subsp. sirjanensis is described as a new subspecies and C. ispahanica subsp. macrocarpa is proposed as a new combination. Finally, C. ispahanica is typified and its chromosome number is reported for the first time, and a new basic chromosome number for C. sect. Rhizocalathium is proposed.